Critical site differences of fusion protein between wildtype and vaccine measles virus strains in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera Ibrahim; Agus Suwandono (Indonesian Pediatric Society, 2011)
Background Measles virus can cause high morbidity and mortality in infants and children. Fusion glycoprotein (F protein) found in the viral envelope is important for the host cell infection mechanism. F protein is immunogenic and may cause specific immune responses in the host. High variability is found in the F protein gene of vaccine viral strains compared to 'Wild type strains. This amino add sequence variability may result in a less specific immune response against other strains, possibly rendering thevaccine to be less effective.Objective To detennine the amino add sequence differences in critical sites of F protein in Mld type and vaccine measles virus strains in Indonesia.Methods We compared amino acid sequences of three genotypes of Mld type measles virus (02, 03 and D9) to those of the vaccine strains, CAM􀀸 70, Schwarz, and Edmonston􀀸wt type measles virus.Resul ts Analysis showed that there were differences at Fl􀀸F2 cleavage site, B cell epitopes, and H protein binding site between the CAM􀀸70 vaccine viral strains and Mld type strains. Schwarz vaccine strain differed from the wild type strains at the H protein binding site. A 03 wild type strain potential glycosylation site was also different from all other strains studied.Conclusion There were differences in the critical sites of F protein between Mld type strains and the CAM􀀸70 and Schwarz vaccine strains.